2017
DOI: 10.21037/jtd.2017.08.43
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair versus replacement in elderly patients: a systematic review and meta-analysis

Abstract: Background: Although mitral valve repair (MVP) is generally accepted as the standard treatment for mitral valve disease, in older patients, there is increasing debate about whether MVP is superior to mitral valve replacement (MVR). We, therefore, performed a meta-analysis to compare MVP vs. MVR in the elderly population. 0.56-0.86). In addition, our study also demonstrated improved 1-year (RR: 1.16, 95% CI: 1.08-1.24) and 5-year (RR: 1.26, 95% CI: 1.13-1.41) survival rates following MVP. There was no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
5
12
0
2
Order By: Relevance
“…Included in a meta-analysis by Shang et al[67] were seven observational clinical studies published after 2000 comparing MVP and MVR in the elderly (aged 70 years or older). Overall, 1809 patients were considered.…”
Section: MVmentioning
confidence: 99%
“…Included in a meta-analysis by Shang et al[67] were seven observational clinical studies published after 2000 comparing MVP and MVR in the elderly (aged 70 years or older). Overall, 1809 patients were considered.…”
Section: MVmentioning
confidence: 99%
“…However, the feasibility and efficacy of MV repair in the elderly population is still debated. Although some retrospective observational studies and meta-analyses have suggested that MV repair might have favorable results in early and long-term outcomes even in the elderly population [310], data obtained from administrative American databases showed a low rate of MV repair (<50%) in those older than 65 years [13,14]. Some operators, especially young surgeons, still considered older patients to be poor surgical candidates for MV repair for multiple reasons: (1) MV repair requires longer CPB and ischemic times, which can affect early and long-term clinical outcomes; (2) elderly patients tend to have a more friable or calcified leaflet and annulus, making repair technically more difficult, increasing the possibility of failure and reoperation; and (3) the shorter life expectancy of elderly patients may decrease the benefit of MV repair over MV replacement [5,8,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Current European and American guidelines recommend mitral valve (MV) repair as the treatment of choice for primary degenerative mitral regurgitation (MR) in the general population [1,2]. However, controversy exists regarding whether MV repair provides the same advantages as MV replacement in terms of operative mortality, long-term survival, and valve-related complications in the elderly population [310]. The aim of this study was to compare the early and long-term clinical outcomes of MV repair and MV replacement in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Подобные состояния требуют коррекции, как первопричины -ишемии, методами реваскуляризации миокарда, так и непосредственно морфофункциональных нарушений работы митрального клапана -протезированием или аннулопластикой [4]. Современные публикации и метаанализы крупных исследований, сравнивающие протезирование и реконструкцию митрального клапана, не могут однозначно рекомендовать тот или иной подход [5][6][7]. В целом большинство подобных работ содержат вывод об отсутствии значимых различий в выживаемости, частоте летальных исходов, ассоциированных с вмешательством, или частоте серьезных неблагоприятных сердечных или цереброваскулярных событий, акцентируя внимание на преимуществах лишь для отдельных групп или по отдельным показателям [6,7].…”
Section: Introductionunclassified
“…Современные публикации и метаанализы крупных исследований, сравнивающие протезирование и реконструкцию митрального клапана, не могут однозначно рекомендовать тот или иной подход [5][6][7]. В целом большинство подобных работ содержат вывод об отсутствии значимых различий в выживаемости, частоте летальных исходов, ассоциированных с вмешательством, или частоте серьезных неблагоприятных сердечных или цереброваскулярных событий, акцентируя внимание на преимуществах лишь для отдельных групп или по отдельным показателям [6,7]. Таким образом, выбор оптимальной хирургической тактики для коррекции тяжелой ИМР в рутинной практике зависит от ряда клинических и субъективных показателей.…”
Section: Introductionunclassified